The Challenges of International EFL Students to Learn English in a Non-English Speaking Country - Oktari Firda Hibatullah (Journal of Foreign Language Teaching and Learning, 2019)
In the recent era, a wider global community has used English for any purpose; one of the most important is academic purposes. In terms of academic purposes, learning English now becomes a must for any students all around the world, specifically EFL students. Focusing on the learning English issue, this research took a rare case about the  EFL students do a study abroad program in a non-English speaking country, especially in the context of English learning problems and strategies. Under a qualitative case study, the researcher addressed two main methods to two international EFL students at a private Islamic university in Yogyakarta, Indonesia. By using reflective essays and interviews as the methods, the data concluded that most of the problems found had similarities to the EFL students’ problems when they study in their home country. Along with the problems, the researcher also discovered strategies done by both of the participants to resolve the problems.